Protective Efficacy of DNA Vaccines against Duck Hepatitis B Virus Infection - Triyatni, M. (American Society for Microbiology, 1998)
The efficacy of DNA vaccines encoding the duck hepatitis B virus (DHBV) pre-S/S and S proteins were tested in Pekin ducks. Plasmid pcDNA I/Amp DNA containing the DHBV pre-S/S or S genes was injected intramuscularly three times, at 3-week intervals. All pre-S/S and S-vaccinated ducks developed total anti-DHBs and specific anti-S antibodies with similar titers reaching 1/10,000 to 1/50,000 and 1/2,500 to 1/4,000, respectively, after the third vaccination. However, following virus challenge, significant differences in the rate of virus removal from the bloodstream and the presence of virus replication in the liver were found between the groups. In three of four S-vaccinated ducks, 90% of the inoculum was removed between <5 and 15 min postchallenge (p.c.) and no virus replication was detected in the liver at 4 days p.c. In contrast, in all four pre-S/S-vaccinated ducks, 90% of the inoculum was removed between 60 and 90 min p.c. and DHBsAg was detected in 10 to 40% of hepatocytes. Anti-S serum abolished virus infectivity when preincubated with DHBV before inoculation into 1-day-old ducklings and primary duck hepatocyte cultures, while anti-pre-S/S serum showed very limited capacity to neutralize virus infectivity in these two systems. Thus, although both DNA vaccines induced high titers of anti-DHBs antibodies, anti-S antibodies induced by the S-DNA construct were highly effective in neutralizing virus infectivity while similar levels of anti-S induced by the pre-S/S-DNA construct conferred only very limited protection. This phenomenon requires further clarification, particularly in light of the development of newer HBV vaccines containing pre-S proteins and a possible discrepancy between anti-HBs titers and protective efficacy.